Perioperative Research into Memory (PRiMe): Cognitive impairment following a severe burn injury and critical care admission, part 1. Issue 5 (August 2018) - Watson, Edward J.R.; Nenadlová, Klára; Clancy, Olivia H.; Farag, Mena; Nordin, Naz A.; Nilsen, Agnes; Mehmet, Ashley R.T.; Al-Hindawi, Ahmed; Mandalia, Sundhiya; Williams, Lisa M.; Edginton, Trudi L.; Vizcaychipi, Marcela P.
Highlights: Patients suffer a significant cognitive deficit after a severe burns injury. These spanned multiple domains including: working memory, delayed recall, attention, executive function and language. Patients reported a reduction in Quality of Life and an increase in symptoms of depression and post-traumatic stress. Abstract: Introduction: An investigation into long-term cognitive impairment and Quality of Life (QoL) after severe burns. Methods: A proof of principle, cohort design, prospective, observational clinical study. Patients with severe burns (>15% TBSA) admitted to Burns ICU for invasive ventilation were recruited for psychocognitive assessment with a convenience sample of age and sex-matched controls. Participants completed psychological and QoL questionnaires, the Cogstate ® electronic battery, Hopkins Verbal Learning, Verbal Fluency and Trail making tasks. Results: 15 patients (11M, 4F; 41 ± 14 years; TBSA 38.4% ± 18.5) and comparators (11M, 4F; 40 ± 13 years) were recruited. Burns patients reported worse QoL (Neuro-QoL Short Form v2, patient 30.1 ± 8.2, control 38.7 ± 3.2, p = 0.0004) and cognitive function (patient composite z-score 0.01, IQR −0.11 to 0.33, control 0.13, IQR 0.47–0.73, p = 0.02). Compared to estimated premorbid FSIQ, patients dropped an equivalent of 8 IQ points (p = 0.002). Cognitive function negatively correlated with burn severity (rBaux score, p = 0.04). QoL strongly correlated with depressive symptoms (Rho = −0.67, p = 0.009) but not cognitive function. Conclusions: Severe burns injuries are associated with a significant, global, cognitive deficit. Patients also report worse QoL, depression and post-traumatic stress. Perceived QoL from cognitive impairment was more closely associated with depression than cognitive impairment.